2011
DOI: 10.2217/nnm.11.143
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Targeting Strategies in Gene Delivery

Abstract: Gene delivery is a process of the insertion of transgenes into cells with the purpose to obtain the expression of encoded protein. The therapeutic application of this process is termed gene therapy, which is becoming a promising instrument to treat genetic and acquired diseases. Although numerous methods of gene transfer have already been developed, including biological, physical and chemical approaches, the optimal strategy has to be discovered. Importantly, it should be effective, selective and safe to be tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 82 publications
0
25
0
Order By: Relevance
“…The lipoplexes easily fuse with the negatively charged cell membrane or are incorporated into cells by endocytosis, which facilitate the transport of DNA through the cell membrane and also protect the DNA from undesirable degradation. [ 34,35 ] Cell adhesive proteins, fi bronectin and gelatin, were added into the mixture of lipofectamine 2000 and pDNA to form the fi nal lipoplex, since previous results showed that these proteins are important for local and highly effi cient transfection of lipoplexes in the reverse transfection technology. [ 30 ] Fibronectin, is an extracellular matrix component that binds to integrins on cell membranes, provides a scaffold for cells and ensures strong cellular adhesion on solid surfaces such as glass, metal, etc.…”
Section: Functionalization Of Abfs With Lipoplexesmentioning
confidence: 99%
“…The lipoplexes easily fuse with the negatively charged cell membrane or are incorporated into cells by endocytosis, which facilitate the transport of DNA through the cell membrane and also protect the DNA from undesirable degradation. [ 34,35 ] Cell adhesive proteins, fi bronectin and gelatin, were added into the mixture of lipofectamine 2000 and pDNA to form the fi nal lipoplex, since previous results showed that these proteins are important for local and highly effi cient transfection of lipoplexes in the reverse transfection technology. [ 30 ] Fibronectin, is an extracellular matrix component that binds to integrins on cell membranes, provides a scaffold for cells and ensures strong cellular adhesion on solid surfaces such as glass, metal, etc.…”
Section: Functionalization Of Abfs With Lipoplexesmentioning
confidence: 99%
“…However, the clinical applications of Lipofectamine and PEI are restricted due to sensitivity and safety issues. Moreover, nonviral carriers can be combined with magnetic nanoparticles in order to improve selectivity and safety of delivery as well as to decrease side effects [14]. In 2002, Scherer and coworkers invented a novel technique termed “magnetofection.” This technique combines different well investigated gene delivery vectors (e.g., retrovirus, Lipofectamine, and PEI) with superparamagnetic iron oxide nanoparticles via salt-induced aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…We concluded a more rapid and efficient release of DNA from magnetic complexes compared to PEI polyplexes [21]. In contrast to DNA/PEI complexes, MNP containing complexes did not enter the nucleus due to strong biotin-streptavidin connections but released the DNA in the perinuclear region [14]. We have recently transferred this approach to transfection of hMSCs with miR, as the latter binds to its target mRNAs in the proximity of the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo , magnetic nanoparticles, carrying genetic material, can be targeted to the site of interest by external magnetic fields [16]. Advantages of this approach are decreased side effects, increased selectivity as well as reduced costs and dosage of the non-viral vector [17,18]. Moreover, cells transfected with magnetic nanoparticles have the potential to be targeted to the region of interest in vivo after transplantation into the organism, thus promoting the effect of cell-based therapies, e.g., in cancer treatment and cardiovascular diseases [19,20].…”
Section: Introductionmentioning
confidence: 99%